Femtosecond laser waveguide and FBG inscription in four-core optical fibre - Theodosiou, Antreas; Ioannou, Andreas; Michael, Polis; Lacraz, Amédéé; Koutsides, Charalambos; Kalli, Kyriacos (My University, 2016)
We present research into the use of femtosecond lasers to develop optical waveguides inscribed in the cladding of singlemode, silica optical fibre (SMF28). The waveguides are inscribed near to the fibre core, coupling light into them evanescently and so behaving as traditional couplers. By carefully controlling the laser parameters we are able to inscribe cladding waveguides with no evidence of damage through ablation. We show that this flexible inscription method can be used as an enabling technology to couple light from single-core fibres to new multi-core optical fibres, and in this work specifically to 4-core fibre. The SMF28 fibre is fusion spliced to the multi-core fibre and using the femtosecond laser we inscribe bridging waveguides from the centrally located single mode fibre core to a selected offset core of the 4-core fibre. To demonstrate the efficiency of the method and the possibility of making new kinds of optical fibre sensors, we inscribe a fibre Bragg grating (FBG) in one of the four fibre cores. The light reflected from the FBG is coupled back to the SMF28 core via bridging waveguide and we recovered the reflection spectrum of the grating using a commercial high-resolution spectrometer.
Keywords: Femtosecond laser; Fibre Bragg grating; Multi-core fibre; Waveguide inscription